The Effectiveness of Problem-Based Learning Model in Physical Education Subjects in Senior High Schools - Maulana, Iqbal; Yopi Hutomo Bhakti (Universitas Pendidikan Ganesha, 2025)
Problem-Based Learning (PBL) is an instructional model that places students at the center of the learning process by presenting real-world problems to be solved. This approach promotes critical thinking, collaboration, and emotional regulation skills, which are highly relevant in the context of Physical Education learning in Senior High Schools. This study aims to evaluate the effectiveness of PBL implementation through a Systematic Literature Review (SLR) approach. Data were collected from the Google Scholar database, focusing on articles published between 2019 and 2023. Out of a total of 378 articles found, 11 were selected based on eligibility criteria, such as relevance to keywords and citation count. The analysis results indicate that PBL is not only effective in improving cognitive learning outcomes and students' motor skills but also enhances motivation, active engagement, teamwork skills, and emotional regulation. Moreover, PBL has been proven to encourage students to connect learning with real-life situations, thereby deepening conceptual understanding and strengthening critical thinking skills. This study recommends the implementation of PBL as an innovative strategy in Physical Education to support students' holistic development. By integrating this approach, the quality of learning is expected to improve significantly. These findings make an important contribution to further research, particularly regarding the development of PBL when combined with technology or digital media to expand its impact.